Association of Posterior Capsular Opacification with Different Type of Intraocular Lenses: A Retrospective Study from Gujarat, India - Shriya Ashish Kotak; Jane Manishkumar Mehta; Samir Bhavsar; Rashi Kochar (JOURNAL OF CLINICAL AND DIAGNOSTIC RESEARCH, 2026)
Introduction: Posterior Capsular Opacification (PCO) is the most common complication following cataract surgery, caused by the proliferation and migration of Lens Epithelial Cells (LECs). Though surgical techniques aim to minimise cortical remnants, the physical and chemical properties of Implanted Intraocular Lenses (IOLs), are increasingly recognised as the primary determinants of capsular clarity. Consequently, identifying specific lens configurations that actively inhibit the cellular mechanisms driving PCO is crucial for minimising secondary laser interventions. Aim: To find the prevalence of PCO in patients coming to eye OPD at a tertiary care hospital and to compare and associate the prevalence of PCO with the type of IOL implanted and other ocular parameters. Materials and Methods: A retrospective study was conducted at Shree Krishna Hospital, Pramukhswami Medical College, Karamsad, Gujarat, India analysing the records of 270 patients who underwent cataract surgery with IOL implantation followed by an Neodymium-doped Yttrium Aluminum Garnet (Nd:YAG) laser capsulotomy. Operative and clinical data such as type of cataract surgery, design and material of IOL and co-morbidities were retrieved from medical records. Statistical analysis was performed using Statistical Package for the Social Sciences (SPSS) version 26.0, using descriptive statistics and the Chisquare test to evaluate associations between categorical variables. Result: The overall prevalence of PCO in this study was 44.4% (n=120/270). The analysis revealed a statistically significant association between the occurrence of PCO and both the material composition and optic design of the implanted IOL. Patients implanted with hydrophilic IOLs exhibited a significantly higher likelihood of developing PCO compared to those receiving hydrophobic IOLs {71.4% (n=60/84) vs 32.3% (n=60/186)}. Similarly, the occurrence of PCO in eyes with round-edged IOLs was markedly greater than in those with square-edged designs {86.7% (n=104/120) vs 13.3% (n=16/120)}. Conclusion: The study revealed a strong association between PCO, material, and IOL design. Specifically, hydrophilic IOLs and those with round-edged were more likely to result in PCO compared to hydrophobic and square-edged IOLs. On the other hand, factors such as patient age, presence of diabetes mellitus, and the type of cataract surgery (phacoemulsification versus manual small incision cataract surgery) showed no significant influence on PCO development.